Chronic disease management: Discussing the perspectives of general practitioners in Italy. (February 2020) - Barsanti, Sara; Guarneri, Francesca
The aim of this paper is to provide an overview of general practitioners' perspectives across key criteria for effective chronic disease management. The study setting is the Tuscany Region in Italy that implemented the Chronic Care Model in 2010 with multidisciplinary team to assist chronic patients. We used the results of a web-based survey of general practitioners (N = 1136) conducted in 2015 to compare the experiences and satisfaction of general practitioners involved (group 1) and not involved (group 2) in the Chronic Care Model. The analysis included all general practitioners, and compared the two groups' perspectives of the different core aspects of Chronic Care Model through conducting an ANOVA analysis and Bonferroni test. General practitioners involved in the Chronic Care Model are found to be more favourably disposed toward measurement and benchmarking, and more satisfied in terms of decision support system. Conversely, no significant differences were found in terms of collaboration with specialists, which remains weak and in terms of community collaboration and involvement. This study provides a detailed investigation of the implementation of Disease Management Programs, by considering the professional point of view.